Contribution of Tahfidz Al-Qur’an Program to Qur’an Hadith Learning Achievement at MTsN 10 Nganjuk - Amiga Putri Minanda; Nazwah Asyro Muharroma; Muh Barid Nizarudin Wajdi (IERA, Islamic Education and Research Academy, 2025)
This study examines the contribution of the Tahfidz Al-Qur’an Program to Qur’an Hadith learning achievement at MTsN 10 Nganjuk. The research background is based on the importance of integrating Qur’anic memorization programs to improve students’ achievement, particularly in subjects directly related to Qur’anic content. This research employed a quantitative approach with a correlational design. The population consisted of all 36 students of class VIII B, selected using a saturated sampling technique. Data for variable X were obtained from the Tahfidz Program questionnaire, while variable Y was taken from Qur’an Hadith report card scores. Data analysis included validity and reliability tests, descriptive statistics, classical assumption tests, and simple linear regression using SPSS version 18. The results showed that the Tahfidz Program was in the moderate category (average score of 70 out of 80), while learning achievement was in the good category (average score of 83.17). Regression analysis revealed a positive and significant influence, with a significance value of 0.008 (< 0.05) and a coefficient of determination of 0.19. Thus, the Tahfidz Program contributed 19% to Qur’an Hadith learning achievement. This study confirms that the Tahfidz Program can be an effective strategy to improve academic achievement while fostering students’ religious character